Recombinant actin-depolymerizing factor of the apicomplexan Neospora caninum (NcADF) is susceptible to oxidation - Baroni, Luciana; Abreu-Filho, Péricles Gama; Pereira, Luiz Miguel; Nagl, Markus; Yatsuda, Ana Patricia (Frontiers in Cellular and Infection Microbiology, 2022)
Neospora caninum is a member of Apicomplexa Phylum and the causative agent of neosporosis, a disease responsible for abortions in cattle. Apicomplexan parasites have a limited set of actin-binding proteins conducting the regulation of the dynamics of nonconventional actin. The parasite actin-based motility is implicated in the parasite invasion process in the host cell. Once no commercial strategy for the neosporosis control is available, the interference in the parasite actin function may result in novel drug targets. Actin-depolymerization factor (ADF) is a member of the ADF/cofilin family, primarily known for its function in actin severing and depolymerization. ADF/cofilins are versatile proteins modulated by different mechanisms, including reduction and oxidation. In apicomplexan parasites, the mechanisms involved in the modulation of ADF function are barely explored and the effects of oxidation in the protein are unknown so far. In this study, we used the oxidants N-chlorotaurine (NCT) and H2O2 to investigate the susceptibility of the recombinant N. caninum ADF (NcADF) to oxidation. After exposing the protein to either NCT or H2O2, the dimerization status and cysteine residue oxidation were determined. Also, the interference of NcADF oxidation in the interaction with actin was assessed. The treatment of the recombinant protein with oxidants reversibly induced the production of dimers, indicating that disulfide bonds between NcADF cysteine residues were formed. In addition, the exposure of NcADF to NCT resulted in more efficient oxidation of the cysteine residues compared to H2O2. Finally, the oxidation of NcADF by NCT reduced the ability of actin-binding and altered the function of NcADF in actin polymerization. Altogether, our results clearly show that recombinant NcADF is sensitive to redox conditions, indicating that the function of this protein in cellular processes involving actin dynamics may be modulated by oxidation.